Interindividual differences in neonatal sociality and emotionality predict juvenile social status in rhesus monkeys. Issue 2 (2nd October 2018) - Wooddell, Lauren J.; Simpson, Elizabeth A.; Murphy, Ashley M.; Dettmer, Amanda M.; Paukner, Annika
Abstract: In humans, socioeconomic status (SES) has profound outcomes on socio‐emotional development and health. However, while much is known about the consequences of SES, little research has examined the predictors of SES due to the longitudinal nature of such studies. We sought to explore whether interindividual differences in neonatal sociality, temperament, and early social experiences predicted juvenile social status in rhesus monkeys ( Macaca mulatta ), as a proxy for SES in humans. We performed neonatal imitation tests in infants' first week of life and emotional reactivity assessments at 2 and 4 weeks of age. We examined whether these traits, as well as the rearing environment in the first 8 months of life (with the mother or with same‐aged peers only) and maternal social status predicted juvenile (2–3 years old) social status following the formation of peer social groups at 8 months. We found that infants who exhibited higher rates of neonatal imitation and newborn emotional reactivity achieved higher social status as juveniles, as did infants who were reared with their mothers, compared to infants reared with peers. Maternal social status was only associated with juvenile status for infant dyads reared in the same maternal group, indicating that relative social relationships were transferred through social experience. These results suggest that neonatal imitation and emotional reactivity may reflect ingrained predispositions toward sociality that predict later outcomes, and that nonnormative social experiences can alter socio‐developmental trajectories. Our results indicate that neonatal characteristics and early social experiences predict later social outcomes in adolescence, including gradients of social stratification. Abstract : Neonatal sociality and temperament, measured in the first month of life, as well as early social experiences across the first 8 months of life, predicted juvenile social status in rhesus macaques (Macaca mulatta), 2‐3 years later. Neonatal characteristics and early social experience may have stable, long‐term effects on the development of social status.